Astudy and Analysis of Geomagnetic Field By using Model of International Geomagnetic Reference Field (IGRF- 2000) - A I- Mahdi, H. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The IGRF model is the empirical representation of the Earth magnetic field recommended for scientific use by the International Association of Geomagnetism and Aeronomy(IAGA). Since the Geomagnetic field has the abi lity to change the orientation of satellite, the strength of Geomagnetic field and its horizontal component have been studied. This paper discusses the phenomenon of the Geomagnetic field intensity and its horizontal component at diferent altitudes and at certain latitudes, the geomagnetic field data is obtained by using IGRF2000 model at Baghdad (44.7 degree East longitude) .